Polarimetric Imaging in the Environment Containing Medium and Object - Wang, Daqian; Wang, Xin; Pan, Peifeng; Gao, Jun (Frontiers in Physics, 2022)
Polarimetric imaging has been studied and applied to the problem of visibility restoration in various scenarios such as haze, mist and underwater. Although studies have shown that under certain conditions, circular polarimetric imaging has certain advantages over linear polarimetric imaging, however, for a complex environment containing both scattering medium and object, the performance of linear and circular polarimetric imaging is affected by many factors. In this paper, the propagation of linear and circular polarized light in the scattering medium is theoretically analyzed, then the simulation experiments under different experimental conditions are carried out and the conclusions are summarized. In order to validate the simulation results, the measurement experiments are carried out in dynamic smoke scenarios with different smoke concentrations. The results show that, the propagation of the polarized light, especially the circular polarized light, is determined by medium conditions. Generally, both the linear and circular polarimetric imaging had an ability to reduce the image degradation caused by smoke, however, under some certain environment conditions, unlike the linear polarized channels, the difference between the orthogonal circular polarized channels may be approached or even reversed, which may limit the circular polarization-based difference imaging and visibility restoration performance.